PELAKSANAAN GADAI SYARIAH PADA PERUM PEGADAIAN SYARIAHCABANG UJUNG GURUN-PADANG - , Suhaimi Irwan, Prof. Dr. Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to describe the implementation of sharia in the mortgage contract Pawnshop Branch Sharia Ujung Gurun Edge Padang and to describe the solution given to the customer defaults, including the future prospects for the pawnshop Islamic Sharia Ujung GurunBranch tip of Padang. This study is the legal research that is descriptive, empirical juridical approach (socio legal Research). The data used are the primary data and secondary data. Primary data obtained from interviews with respondents. While the secondary data obtained from the literature and primary legal materials, legal materials secondary, and tertiary legal materials. The overall data obtained in the qualitative analysis. Sharia Pawnshop Transaction on contract signing marked with SBR (Proof Rahn) which has been provided by the Islamic pawnshop. By signing the contract with rights and obligations between rahin and murtahin.In the implementation of the practice of consent and Kabul, which is very rarely harmonious agreement executed by the parties. The solution given by the Islamic pawnshop to pawnshop customers are defaulting Islamic provide gracepriode facilities, delay the auction, and automatic re pawning. The benefits are rahin Execution postponed auctions, free auctions, and allow time to seek fresh funds rahin. The prospect of Shariah Pawnshop Branch tip Ujung Gurun Padang increased relative to the addition of proven customer and increase lending to the public.